PENGARUH CUSTOMER RATING, PENGIKLANAN DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA PENGGUNA SHOPEE DI KOTA BATAM - Chandra, Andy; Rustam, Triana Ananda (LPPM Universitas Putera Batam, 2022)
Many factors that be conducted to a decrease in visitors which in essence will also affect the purchasing decisions of Shopee users. Researchers take quantitative methods in their preparation. The population of the researchers decided that the population of Lubuk Baja Sub-district whose number was unknown and used a questionnaire to get a response. A sample of 204 was determined based on the Jacob Cohen formula. Applying purposive sampling and non-probability sampling. In this research, the researcher uses research development research to add new variables and indicators to previous research and refine it. This research also takes the type of research with a quantitative approach and uses the SPSS version 26 analysis tool. The results of tests carried out through SPSS version 26 prove significantly that the customer rating has no influence on purchasing decisions. The multiple regression test output is 0.175. The T_count value is 1,826 T_(table )1,971 with the significance value is 0,069 from 0,05. The results of tests conducted through SPSS version 26 prove significantly that advertising has an influence on purchasing decisions. The multiple regression output is 0.283. The T_count value is 3.351 T_(table )1.971 with the significance value is 0.01 from 0.05. The results of tests conducted through SPSS version 26 prove that simultaneously customer rating, advertising and service quality have a significant influence on purchasing decisions. The f_count value is 14,565 f_(table)2.65 and the significance value is 0.00 from 0.05. Partially, the customer rating does not have a significant effect on purchasing decisions. partially advertising and service quality have a significant influence on purchasing decisions. In this study, the variables of customer rating, advertising and service quality simultaneously have a significant influence on purchasing decisions for Shopee users in Batam City.